Non-peptidergic small diameter primary afferents expressing VGluT2 project to lamina I of mouse spinal dorsal horn - Clarke Jennifer N; Anderson Rebecca L; Haberberger Rainer V; Gibbins Ian L (SAGE Publishing, 2011)
Abstract Background Unmyelinated primary afferent nociceptors are commonly classified into two main functional types: those expressing neuropeptides, and non-peptidergic fibers that bind the lectin IB4. However, many small diameter primary afferent neurons neither contain any known neuropeptides nor bind IB4. Most express high levels of vesicular glutamate transporter 2 (VGluT2) and are assumed to be glutamatergic nociceptors but their terminations within the spinal cord are unknown. We used in vitro anterograde axonal tracing with Neurobiotin to identify the central projections of these putative glutamatergic nociceptors. We also quantitatively characterised the spatial arrangement of these terminals with respect to those that expressed the neuropeptide, calcitonin gene-related peptide (CGRP). Results Neurobiotin-labeled VGluT2-immunoreactive (IR) terminals were restricted to lamina I, with a medial-to-lateral distribution similar to CGRP-IR terminals. Most VGluT2-IR terminals in lateral lamina I were not labeled by Neurobiotin implying that they arose mainly from central neurons. 38 ± 4% of Neurobiotin-labeled VGluT2-IR terminals contained CGRP-IR. Conversely, only 17 ± 4% of Neurobiotin-labeled CGRP-IR terminals expressed detectable VGluT2-IR. Neurobiotin-labeled VGluT2-IR or CGRP-IR terminals often aggregated into small clusters or microdomains partially surrounding intrinsic lamina I neurons. Conclusions The central terminals of primary afferents which express high levels of VGluT2-IR but not CGRP-IR terminate mainly in lamina I. The spatial arrangement of VGluT2-IR and CGRP-IR terminals suggest that lamina I neurons receive convergent inputs from presumptive nociceptors that are primarily glutamatergic or peptidergic. This reveals a previously unrecognized level of organization in lamina I consistent with the presence of multiple nociceptive processing pathways.